Die Reformasie en Skrifinterpretasie: Die nuwe wat die Reformasie gebring en ook moontlik gemaak het - Labuschagne, Kobus (HTS teologiese studies, 2008)
The Reformation and the interpretation of the Scriptures The aim of this article is to emphasize new trends in the interpretation of the Scriptures that were brought about by the Reformation and that were consequently made possible for the future. Reformation thinking and modern and contemporary thinking are compared and analyzed in order to establish the consequences of the openness created by the Reformation, in response to Medieval objectified thinking in which the Church always had a final and an arrived definition and statement. What should therefore be avoided is the misconception that Reformation thinking represented an arrived and stagnated way of doing theology.